Physical and chemical restraints questionnaire: development and validation study - Subramaniam, Tirumal (2020)
Physical and chemical restraints have been used frequently in Emergency Departments to deal with aggressive patients irrespective of the aetiology. As much as application of physical and chemical restraints can render the vicinity to be safe for patient and healthcare personnel, it still possess inherent danger to patient. There appears no uniform guideline on applying restraints to patients. This study attempts to develop and validate a questionnaire to assess knowledge of nurses, medical assistants and doctors on chemical and physical restraints. This Knowledge Questionnaire on Patient’s Physical and Chemical Restraint (KQPPCR-BM) is expected to assess knowledge of target group, so that steps can be taken to improve their knowledge and can be used for pre-test and post-test assessment. This study consist of two phases, questionnaire development and psychometric assessment. Questionnaire development consist of content validity with five expert panel and face validity using 30 respondents. The second phase was the psychometric assessment phase using Item Response Theory (IRT) using 151 respondents.